Handling and processing of pathology samples of suspected or confirmed COVID-19 patient - Karki, Diksha; Upadhyaya, Paricha; Adhikari, Purbesh; Dahal, Mona; Yadav, Jitendra Kumar (Journal of Pathology of Nepal, 2020)
The SARS-CoV-2 has emerged as a major public health concern. Human to human transmission has been confirmed via droplets, contaminated surfaces, and hands. All the staffs and personnel working in the laboratory are also at risk of contracting this infection, especially during the handling and processing of samples from suspected or confirmed patients of COVID-19. With no definite treatment and vaccine in sight, the way forward is to break the chain of transmission by eliminating the risk of exposure to laboratory staffs by proper handling and processing of all the samples in an appropriate containment level laboratory, proper use of personal protective equipment with special attention on disposal and decontamination of work surfaces.